High RPS3A expression correlates with low tumor immune cell infiltration and unfavorable prognosis in hepatocellular carcinoma patients - Zhou, Chenhao (Am J Cancer Res, 2020)
Despite the use of immune checkpoint blockade (ICB) therapy for hepatocellular carcinoma (HCC), developing more effective immunotherapy and predicting HCC’s response to ICB therapy remain top priorities. Ribosomal protein S3A (RPS3A) is a multifunctional molecule, but its association with tumor immune cell infiltration and prognosis in HCC patients is unknown. Thus, we aimed to investigate the correlation of RPS3A with HCC immune cell infiltration and prognosis to explore novel therapeutic strategies and prognostic biomarkers for this disease. Here, we showed that RPS3A expression levels were higher in HCC cell lines and samples than in normal hepatocytes and adjacent tumor-free tissues, respectively, and patients with high RPS3A expression had worse overall and recurrence-free survival durations than did patients with low expression. Moreover, single-sample gene set enrichment analysis (ssGSEA) and immunohistochemistry demonstrated a strongly negative correlation between RPS3A expression and tumor immune cell infiltration. Meanwhile, RPS3A was revealed to be positively correlated with that of most examined immune checkpoint molecules. GSEA also suggested that high RPS3A expression promoted the biological processes related to tumorigenesis, metastasis, and immunosuppression. Finally, RPS3A-based nomograms were constructed and exhibited better predictive accuracy for HCC prognosis and more net clinical benefits when compared with traditional prognosis-prediction staging systems. In short, these findings suggest that high RPS3A expression correlates with low tumor immune cell infiltration and poor prognosis in HCC patients. Furthermore, RPS3A-based nomograms are robust HCC prognostic predictors. RPS3A therefore may serve as a therapeutic target in and predict the efficacy of ICB therapy for HCC.